CHALLENGES AND SOLUTIONS OF TECHNOLOGY IN FINANCIAL RECORDING SMEs: SYSTEMATIC LITERATURE REVIEW - Sri Hastutik; Dian Rokhmawati; Rachma Yuliana; Mohammad Dullah (Program Studi Akuntansi Institut Teknologi dan Bisnis Asia Malang, 2026)
This study aims to identify the difficulties faced by SMEs in financial record-keeping and to explain the role of technology as a solution. The method used is a Systematic Literature Review (SLR) by examining Scopus-indexed articles from 1957-2023. The synthesis results reveal six main obstacles, namely technical-operational, resource-based, regulatory and standards, management and strategy, technology and innovation, as well as financial-economic. The most prominent technological solutions include standard training and education, implementation of accounting information systems and IT support, adoption of cloud accounting, use of accounting software or applications, and integration of technology into accounting management strategies. Another significant finding is the still limited discussion of financial data security strategies for SMEs, even though digitalization of financial records increases the risk of data breaches, cyberattacks, and loss of business information. This study concludes that SMEs need to adopt financial record-keeping technology that is efficient, affordable, user-friendly, and secure, accompanied by increased accounting literacy and relevant policy support.